P522 Expression of markers of early atherosclerosis in inflammatory bowel disease: a prospective cohort of a single referral centre. (25th January 2019) - Scrivo, B; Cilluffo, M G; Tuttolomondo, A; Torres, D; Calvaruso, V; Pinto, A; Cappello, M
Abstract: Background: Recent epidemiological studies report an association between ischaemic vascular disorders and inflammatory bowel disease (IBD). In a previous study we have shown increased expression of surrogate markers of early atherosclerosis (ATS), such as aortic stiffness and intima media thickness (IMT) in a homogeneous cohort of IBD patients, in spite of absence of traditional risk factors for ATS, suggesting a role for chronic inflammation. The aim of this study was to assess prospectively modifications of IMT and arterial stiffness in a longitudinal study on the same cohort, in relation to therapy and disease characteristics. Methods: 39 patients with IBD (14 ulcerative colitis and 25 Crohn's disease) underwent a second clinical, bio-humoral and instrumental assessment after a mean period of 4.8 ± 0.3 years. Carotid IMT was evaluated by using high-resolution B-mode ultrasonography. Arterial stiffness was assessed by measurement of carotid-femoral Pulse Wave Velocity (cf-PWV) and Augmentation Index (AIx). Results: We found a statistically significant increase in body mass index (22.44 kg/ m2 at baseline vs. 23.39 kg/ m2 at last follow-up visit, p = 0.043), white blood cell count (7339.05/mmc vs. 8291.28 mmc, p = 0.015) and total cholesterol (160.79 mg/dl vs. 172.08 mg/dl, p = 0.028); while a statistically significant reduction in glycaemia (88.69 mg/dl vs. 83.90 mg/dl, p = 0.019 was observed. No statistically significant variation was observed respect the AIx and carotid IMT; while an average increase in cf-PWV values was observed (8.67 m/s vs. 9.19 m/s, p = 0.129), but without reaching statistical significance. As far as concerns the other hemodynamic parameters, we found a trend in improvement of PAD (diastolic arterial pressure) and PAM (mean arterial pressure): respectively 75.31 mmHg vs. 71.15 mmHg, p = 0.064; 89.51 mmHg vs. 85.13, p = 0.062). No statistically significant difference was found for PAS (systolic blood pressure). On logistic regression analysis, the only variable that was able to influence the worsening of cf-PWV is the duration disease ( p = 0.048). Conclusions: in our prospective cohort of IBD patients there was no significant increase in the expression of surrogate markers of ATS, except cf-PWV which did increase over time . Disease duration was the only variable, among those evaluated, able to predict the worsening of cf-PWV. ATS in IBD is a progressive complication, however progression is slow and the timing of surveillance measures is yet to be established.